Evaluation of the shrinkage and fracture properties of hybrid Fiber-Reinforced SAP modified concrete. (30th September 2020) - Fan, Juntao; Shen, Aiqin; Guo, Yinchuan; Zhao, Ming; Yang, Xiaolong; Wang, Xuhui
Highlights: The mechanical properties of hybrid fiber-reinforced SAP modified concrete was studied. The rule of shrinkage development of reinforced hybrid fiber-reinforced SAP modified concrete was investigated. The fracture properties of hybrid fiber-reinforced SAP modified concrete were evaluated. The mechanism of hybrid fiber-reinforced SAP modified concrete was analyzed. Abstract: This study investigated the shrinkage and fracture properties of superabsorbent polymers (SAP)-modified concrete with and without hybrid fibers. For this purpose, uniaxial compressive, four-point bending, three-point bending, dry shrinkage and plastic cracking tests were carried out on specimens produced using hybrid fiber and SAP. In addition, microstructural analysis was performed using scanning electron microscopy (SEM) to reveal the underlying mechanisms increasing the toughness and cracking resistance of the hybrid fiber-reinforced SAP modified concrete. The results showed that the addition of the hybrid fiber compensated for the strength loss caused by the SAP and effectively increased the strength of the concrete. In addition, the fracture process of the hybrid fiber -reinforced SAP modified concrete exhibited a better toughness than that of SAP modified concrete. Compared with that of SAP modified concrete, the fracture energy was increased by 105.95%, and the total cracking area per unit area was reduced by 73.7%. The addition of both the hybrid fiber and SAP significantly reduced the shrinkage of the concrete, mainly by decreasing the shrinkage rate of the concrete and accelerating the time required for the concrete shrinkage to stabilize. In light of the SEM images, it was suggested that the SAP transported a portion of free water into the concrete and promoted the hydration reaction. The hybrid fiber improved the internal pore structure of the concrete and acted as a reinforcement in the concrete. In general, the SAP and hybrid fiber worked together to increase the toughness and cracking resistance of the concrete.